Challenge in a mathematics classroom: Students' motivation and strategies in project-based learning - Meyer, Debra K.; Turner, Julianne C. (Elementary School Journal, 1997)
Presents information on a study which looked at several fourth and sixth grade students' motivation during project-based mathematics instructions in a classroom. Speculation on the patterns of motivation and behavior; Methodology used to conduct the study; Information on the results of the study.
Keywords: apprentissage par projet